LITERASI MEDIA BERBASIS KEARIFAN LOKAL MASYARAKAT BALI - Darmastuti, Rini; Purnomo, Jusuf Tjahjo; Utami, Birmanti Setia; Yulia, Hanita (Faculty of Communications Science, Dr. Soetomo University, 2019)
This research aims to describe the Balinese local wisdom as the groundwork for media literacy and to build media literacy model. The observations and in-depth interviews to Balinese prominent leaders were conducted in his qualitative research. The results show that (1) Nawangleh and Tri Hita Karana are the Balinese local wisdom; (2) The principle of Nawangleh and Tri Hita Karana becomes the basis for filtering, sorting, and choosing the messages shown on the television; (3) The opinion leaders that convey the messages of media literacy are Kelian Adat and Sanggar’s mentors (housewives), karang taruna’s leaders (teenagers), and school teachers (children).